Relationship Between Chronotype With Emotional Eating, Eating Disorder Risk and Depression: A Cross-Sectional Study - Kübra Esin; Feride Ayyıldız (SAGE Open, 2024)
Chronotype is defined as individuals’ preferences regarding the timing of their sleep and wake cycle. An individual’s chronotype is associated with many factors such as age, sex, and lifestyle. This study was conducted to evaluate the relationship between chronotype and emotional eating,depression, anxiety, stress, body weight, eating disorder risk, and life satisfaction in university students. This present study included 511 Turkish university students with a mean age of 20.0 ± 1.93 years. The anthropometric measurements (body weight, and height) were recorded. Additionally, the Morningness-Eveningness Questionnaire (MEQ), the Emotional Eater Questionnaire (EEQ), the Sick, Control, One stone, Fat, Food (SCOFF) Questionnaire, the Depression, Anxiety, Stress Scale-21 (DASS-21), and the Contentment with Life Assessment Scale (CLAS) were used to collect data. The evening-type individuals had significantly higher total EEQ and DASS-21 subscale scores than the morning-type individuals. The morning-type individuals had significantly higher total CLAS scores than the evening-type individuals. There was no significant difference between the groups in terms of their SCOFF total scores and BMI values. This showed that chronotype is related to emotional eating, depression, anxiety, stress, and life satisfaction in university students, but there is not related to the risk of eating disorders and BMI. The regulation of the circadian system will be useful for improving eating behavior and mood, as well as weight loss programs. It is thought that further long-term follow-up studies with different samples would contribute to this field.